Transient changes in molecular geometries and how to model them : simulating chemical reactions of metal complexes in solution to explore dynamics, solvation, coherence, and the link to experiment /: simulating chemical reactions of metal complexes in solution to explore dynamics, solvation, coherence, and the link to experiment. ([2015]) - Dohn, Asmus Ougaard
No abstract available